2016
DOI: 10.1021/acscatal.6b01424
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Modified Carbon Nano-Materials as Stable Catalysts for Phosgene Synthesis

Abstract: The carbon-catalyzed reaction of Cl2 and CO constitutes the most important industrial route to phosgene. Although defects in carbon lead to surface chemical reactions, direct polarization of C-heteroatom bonds induces a more successful Cl2 catalytic activation, the rate-determining step in the overall catalytic cycle. The interplay between the electron-donating and -withdrawing ability of the incorporated nitrogen substituents on the formation and stabilization of active sites was examined by X-ray photoelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 58 publications
2
26
0
Order By: Relevance
“…For r-SWCNH-ox-1.5, we observed the appearance of N-H bonds at 399.8 eV, pyrrolic or amine moieties at 400.2 and 400.6 eV, and quaternary N at 401.8 eV. 64,70,71 We observed the hydrophilization of the SWCNH surface by the creation of surface oxides. The ratio of C 1s/O 1s peaks decreases rapidly aer a short oxidation process (aer 0.5 h), from 15.110 to 4.143, and subsequently changes during a longer oxidation time, reaching a value of 2.603 for SWCNH-ox-3 (Table 2) and a value of 4.05 for r-SWCNH-ox-1.5.…”
Section: Methodsmentioning
confidence: 75%
“…For r-SWCNH-ox-1.5, we observed the appearance of N-H bonds at 399.8 eV, pyrrolic or amine moieties at 400.2 and 400.6 eV, and quaternary N at 401.8 eV. 64,70,71 We observed the hydrophilization of the SWCNH surface by the creation of surface oxides. The ratio of C 1s/O 1s peaks decreases rapidly aer a short oxidation process (aer 0.5 h), from 15.110 to 4.143, and subsequently changes during a longer oxidation time, reaching a value of 2.603 for SWCNH-ox-3 (Table 2) and a value of 4.05 for r-SWCNH-ox-1.5.…”
Section: Methodsmentioning
confidence: 75%
“…Gupta et al [178] reported an effective method for the preparation of phosgene gas by nitrogen-modified carbon nanomaterials, which was derived from the N-modified polymer material. The incorporation of active nitrogen into graphitic carbon materials resulted in the formation of porous carbon catalysts that are active and stable for the generation of phosgene (COCl 2 ) with very high selectivity.…”
Section: Scheme 19mentioning
confidence: 99%
“…Although the process of phosgene production [3,4], the kinetics of the reaction [5][6][7][8] and catalytic active commercial activated carbons for this reaction are well investigated [9][10][11], there are only a few mechanistic studies. Noteworthy are the studies by Lercher and co-workers, who propose an Eley-Rideal mechanism for the formation of phosgene [12][13][14]. There, the Cl 2 forms a charge-transfer complex with the activated carbon surface, before the Cl-Cl bond is cleaved by a CO molecule attacking from the gas phase.…”
Section: Introductionmentioning
confidence: 99%